Acetylcholinesterase activity measurement and clinical features of delirium - Jackson, T.A.; Moorey, H.C.; Sheehan, B.; Maclullich, A.M.J.; Gladman, J.R.F.; Lord, J.M. (Karger, 2017)
Aims: Cholinergic deficiency is commonly implicated in the pathophysiology of delirium. We aimed to investigate the relationship between directly measured serum AChE activity and (1) clinical features of delirium and (2) outcomes, among older hospital patients with delirium. Methods: Hospitalized patients with delirium were recruited and delirium motor subtype, severity and duration of delirium were measured. Serum AChE activity was measured using a colorimetric assay. Results: The mean AChE activity for the whole sample was 2.46 μmol/μml/min (SD 1.75). Higher AChE activity was associated with increased likelihood of hypoactive delirium rather than the hyperactive or mixed subtype (OR 1.98, CI 1.10-3.59). Conclusion: Higher AChE activity was associated with hypoactive delirium, but did not predict outcomes. Simple enhancement of cholinergic neurotransmission may not be sufficient to treat delirium